2012
DOI: 10.1177/0956797612441220
|View full text |Cite
|
Sign up to set email alerts
|

Brief Wakeful Resting Boosts New Memories Over the Long Term

Abstract: A brief wakeful rest after new verbal learning enhances memory for several minutes. In the research reported here, we explored the possibility of extending this rest-induced memory enhancement over much longer periods. Participants were presented with two stories; one story was followed by a 10-min period of wakeful resting, and the other was followed by a 10-min period during which participants played a spot-the-difference game. In Experiment 1, wakeful resting led to significant enhancement of memory after a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

31
304
9

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 141 publications
(344 citation statements)
references
References 15 publications
31
304
9
Order By: Relevance
“…Placing individuals within an environment that postpones RI does seem to have a positive effect on retention. These findings support Dewar, Alber et al (2012), who found a beneficial effect of wakeful rest in normally aging adults, along with some of the earliest experiments examining the temporal gradient of RI (Landauer, 1974;Müller & Pilzecker, 1900;Skaggs, 1925;Spencer, 1924). Given Dewar, Alber et al's sample, there was concern that rest might only help those who are already more vulnerable to forgetting, but the present data dispel this suggestion and show that wakeful rest lessens forgetting in younger adults too.…”
Section: Discussionsupporting
confidence: 44%
See 4 more Smart Citations
“…Placing individuals within an environment that postpones RI does seem to have a positive effect on retention. These findings support Dewar, Alber et al (2012), who found a beneficial effect of wakeful rest in normally aging adults, along with some of the earliest experiments examining the temporal gradient of RI (Landauer, 1974;Müller & Pilzecker, 1900;Skaggs, 1925;Spencer, 1924). Given Dewar, Alber et al's sample, there was concern that rest might only help those who are already more vulnerable to forgetting, but the present data dispel this suggestion and show that wakeful rest lessens forgetting in younger adults too.…”
Section: Discussionsupporting
confidence: 44%
“…This may be more evident when there is a degree of overlap between the memory and distractor tasks - In summary, whilst Dewar, Alber et al (2012) found that resting had a prolonged positive influence on retention, Dewar et al's (2009) data showed that brief phases of rest did not preserve retention rates in participants with intact memory. Studies investigating the temporal gradient of RI during the early twentieth century were mixed, and other recent literature examining wakeful rest and minimal RI has primarily focussed on patients with amnesia and other forms of cognitive impairment (e.g.…”
Section: Introductionmentioning
confidence: 91%
See 3 more Smart Citations